Environmental impacts and resource use of Australian beef and lamb exported to the USA determined using life cycle assessment. (1st May 2015) - Wiedemann, Stephen; McGahan, Eugene; Murphy, Caoilinn; Yan, Ming-Jia; Henry, Beverley; Thoma, Greg; Ledgard, Stewart
Abstract: Australia is one of the two largest exporting nations for beef and lamb in the world and the USA is a major export market for both products. To inform the Australian red meat industry regarding the environmental performance of exported food products, this study conducted the first multi-impact analysis of Australian red meat export supply chains including all stages through to warehousing in the USA. A large, integrated dataset based on case study farms and regional survey was used to model beef and lamb from major representative production regions in eastern Australia. Per kilogram of retail-ready red meat, fresh water consumption ranged from 441.7 to 597.6 L across the production systems, stress-weighted water use from 108.5 to 169.4 L H2 O-e, fossil energy from 28.1 to 46.6 MJ, crop land occupation from 2.5 to 29.9 m 2 and human edible protein conversion efficiency ranged from 7.9 to 0.3, with major differences observed between grass finished and grain finished production. GHG emissions excluding land use and direct land use change ranged from 16.1 to 27.2 kg CO2 -e per kilogram, and removals and emissions from land use and direct land use change ranged from −2.4 to 8.7 kg CO2 -e per kilogram of retail retail ready meat. Process based life cycle assessment shows that environmental impacts and resource use were highest in the farm and feedlot phase. Transportation contributed ≤5% of greenhouse gas emissions, water and land, confirming that food miles is not a suitable indicator of environmental impacts for red meat transported by ocean shipping. The contribution of international transportation to total energy demand was higher, ranging from 14 to 23%. These beef and lamb supply chains were found to rely on small volumes of water from stressed water catchments, and occupied only small amounts of crop land suited to other food production systems. Production of high quality protein foods for human consumption used only small amounts of protein from human edible grain. Highlights: This is the first multi-impact analysis of Australian red meat supply chains to the USA. International transportation contributed ≤5% of GHG, water and land impacts. Grass-fed red meat used small areas of arable land and relied on modest inputs of human edible protein. Volumetric and stress weighted water use assessments indicate low impacts from Australian red meat.